Exploration of Subjective Well-Being in Parents of Children with Special Needs in Inclusive School MIM X Surakarta - Desanti, Arintya Nur; Hertinjung, Wisnu Sri (Universitas Muhammadiyah Surakarta, 2025)
One of the blessings given by God is the gift of offspring, which is a manifestation of His divine will. Therefore, becoming a parent requires a sincere heart to accept the path that has been chosen, including the role of being a parent to a child with special needs (CWSN). This study aims to explore the Subjective Well-Being (SWB) of parents of CWSN by understanding the depiction of SWB, the influencing factors, and the parents' lived experiences in caring for their children. This research employs a qualitative method with a phenomenological approach. The study involved three informants who are parents of CWSN over the age of three and who serve as the child's primary caregivers. Data collection was conducted through interviews. The data were analyzed using the Miles and Huberman model, and data validity was ensured through data triangulation. The findings indicate that the depiction of SWB varied among informants but tended to be influenced by external protective and risk factors. Protective factors include education, employment, family functioning, income, number of children, and social support. Risk factors include challenges related to the severity of the child's condition, financial limitations, and negative perceptions of the child. Preparation.This study can contribute to society, policymakers and professionals by encouraging the maximization of protective factors that can be provided to parents, thereby helping to improve the Subjective Well-Being of parents of children with special needs.